Magnetic Nanocomposite Hydrogels for Directing Myofibroblast Activity in Adipose‐Derived Stem Cells. Issue 4 (22nd February 2021) - Islam, Md Shariful; Molley, Thomas G.; Ireland, Jake; Kruzic, Jamie J.; Kilian, Kristopher A.
Abstract : Dynamic cell‐culture materials that can change mechanical properties in response to extrinsic stimuli are emerging as promising tools for cell and tissue engineering research. However, most of these techniques involve a one‐way stiffening or softening through changes in the materials chemistry, which does not allow reversibility. Here, the incorporation of superparamagnetic iron‐oxide nanoparticles within poly(ethylene glycol) hydrogels as dynamic cell culture materials is demonstrated. Using simple permanent magnets and adipose‐derived stem cells, a near twofold increase in cell spread area and an accompanying 20% enrichment in cells expressing alpha‐smooth muscle actin is seen. This platform provides a means to study relationships between dynamic stiffening and cell behavior, using permanent magnets and clinically viable composite materials, with scope for use as a tool to enrich the myofibroblast population in stromal cells. Abstract : Incorporation of superparamagnetic iron‐oxide nanoparticles within poly(ethylene glycol) hydrogels results in near twofold increase in adipose‐derived mesenchymal stem cells spread area and an accompanying 20% enrichment in cells expressing alpha‐smooth muscle actin. This platform may be used to enrich the myofibroblast population in stromal cells for fundamental studies and tissue engineering.